Moving loads : dynamic analysis and identification techniques - Law, Siu-Seong.; Zhu, Xin-Qun. (London : CRC Press, 2011)
'Moving load problems occur in a wide variety of applications: rail mechanics, dynamics of computer tapes, floppy and hard discs, automotive and aircraft braking systems, belt drives, web winding and transport. Some typical moving load problems are the vibration of track, bridge or ground excitation from travelling vehicles, and noise and vibration from spinning computer hard discs and during machining processes in manufacturing. As modern lightweight and high strength materials continue to be very popular in engineering, it is expected that vibration and instabilities problems due to moving loads will remain important. This volume treats the fundamentals of moving loads problems with accurate identification and computational efficiency. It starts with detailed descriptions of the dynamic behavior of continuous beam, beam-slab type bridge deck and multi-box spline bridge decks under the passage of moving loads. The second part addresses moving load identification problems with both simple methods for universal application and with specialized techniques. A final chapter treats problems associated with the practical application of moving load identification techniques'--
'Moving load problems occur in a wide variety of applications: rail mechanics, dynamics of computer tapes, floppy and hard discs, automotive and aircraft braking systems, belt drives, web winding and transport. Some typical moving load problems are the vibration of track, bridge or ground excitation from travelling vehicles, and noise and vibration from spinning computer hard discs and during machining processes in manufacturing. As modern lightweight and high strength materials continue to be very popular in engineering, it is expected that vibration and instabilities problems due to moving loads will remain important. This volume treats the fundamentals of moving loads problems with accurate identification and computational efficiency. It starts with detailed descriptions of the dynamic behavior of continuous beam, beam-slab type bridge deck and multi-box spline bridge decks under the passage of moving loads. The second part addresses moving load identification problems with both simple methods for universal application and with specialized techniques. A final chapter treats problems associated with the practical application of moving load identification techniques'--
Includes bibliographical references (p. [293]-304) and index.
Keywords: Live loads; Structural dynamics